1995
DOI: 10.1016/0002-9149(95)90061-6
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine: In vitro influence on heart mitochondrial function

Abstract: The mechanism of action of the antianginal trimetazidine (TMZ) remains largely unknown. In cultured rat ventricular myocytes in physiologic conditions, TMZ (5 x 10(-4) M) reduced the plateau potential level, the upstroke velocity, and the spontaneous action potential rate. When the cardiomyocytes were submitted to hypoxia (150 or 240 minutes) in a glucose-free medium, treatment with TMZ largely prevented the hypoxia-induced electromechanical alterations, i.e., the decrease in plateau amplitude, in resting memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…TMZ at 5.10-J M was very efficient in preventing the shortening of the AP duration induced by substrate-free hypoxia. According to our previous results, however, TMZ at 5.10" M did not significantly attenuate the hypoxia-induced decrease in intracellular ATP content (Fantini et al, 1994;Demaison et al, 1995). Since substrate-free hypoxia causes an intracellular ATP drop in our model (Chevalier et al, 1990), the hypoxia-induced shortening in AP could be linked to the activation of an ATP-sensitive potassium conductance at low ATP levels (Findlay, 1994).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…TMZ at 5.10-J M was very efficient in preventing the shortening of the AP duration induced by substrate-free hypoxia. According to our previous results, however, TMZ at 5.10" M did not significantly attenuate the hypoxia-induced decrease in intracellular ATP content (Fantini et al, 1994;Demaison et al, 1995). Since substrate-free hypoxia causes an intracellular ATP drop in our model (Chevalier et al, 1990), the hypoxia-induced shortening in AP could be linked to the activation of an ATP-sensitive potassium conductance at low ATP levels (Findlay, 1994).…”
Section: Discussionmentioning
confidence: 46%
“…was able to maintain electrical and contractile activity of isolated cardiac muscle cells submitted to substrate-free hypoxia. It can be suggested that the influence of TMZ (5.10 M ) on cell electrophysiology and contractility may represent the functional correlates of a nonspecific membrane effect (Devynck et al 1993) and/or of its intracellular metabolic effects (Demaison et al, 1995). TMZ displayed indeed a depressive action on the V, , , and apparent calcium and potassium blocking potentialities, which were already apparent in basal normoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of FA oxidation by glycerol, observed in this study, may also result from the inhibition of long-chain 3-ketoacyl-CoA thiolase by the acetyl-CoA derived from glycerol oxidation, which increases intracellular acetylCoA, since glucose oxidation is not affected (5). The cardiac function in ischemic conditions and the functional recovery after reperfusion are known to be improved by decreasing the contribution of FAs to cardiac energy (2,7,11,14).…”
Section: Discussionmentioning
confidence: 64%
“…**P Ͻ 0.01. ***P Ͻ 0.001. diabetes is associated with the long-chain acyl-CoA stimulation of CPT-1 and the acceleration of the production of NADH and acetyl-CoA with consequent inactivation of PDH (2,7,14). Conversely, the reduction of ␤-oxidation by glycerol may favor PDH activation (5), which may, in turn, improve the coupling between glycolysis and glucose oxidation and decrease cellular protons and acidosis and hence calcium overload (12,17).…”
Section: Discussionmentioning
confidence: 99%